More Picture-Perfect Science Lessons : Using Childrens Books to Guide Inquiry K-4. - Morgan, Emily (National Science Teachers Association (NSTA), 2007)
Teachers raved when NSTA Press published Picture-Perfect Science Lessons in 2005. They loved its lively mix of kid-magnet books, Standards-based science content and ready-to-teach lessons. So what could be more perfect? More Picture-Perfect Science Lessons! This volume offers 15 new lessons that combine picture books and inquiry to develop students interest in science and reading.